Perancangan Video Pembelajaran Matematika Keuangan Menggunakan Metode Multimedia Development Life Cycle (MDLC) - Tanjung, Rovidatul Hikmah; Damayanti, Fera (Universitas Islam Negeri Sumatera Utara, 2025)
The advantages of learning videos are able to present independent learning with time flexibility and precisely leaving behind traditional teaching that relies on textbooks and lectures in the classroom. In addition, learning videos that are packaged with attractive visual elements such as the use of animation can increase students' motivation in learning. The purpose of this study was to design a financial mathematics learning video using the Multimedia Development Life Cycle (MDLC) method. This method consists of six stages, namely: concept, design, collection of materials, creation, testing, and distribution. Learning videos were tested using alpha testing and beta testing to assess the feasibility of the multimedia created. Alpha testing was carried out on two content experts with the results of the learning video feasibility of